ASSESSMENT OF THE WATER ABSORPTION DECREASE ABILITY TREATMENT ON RECYCLED AGGREGATE CONCRETE OF CALCITE PRECIPITATED BACTERIA ISOLATED IN VIETNAM - Kien, Tran Trung; Dao, Duong Thi Hong; Loan, Le Quynh; Nhung, Vu Thi Tuyet; Ngoc, Tran Thi My; Tan, Tran Binh; Dan, Phan Van; Dung, Nguyen Hoang (HUIT Journal of Science, 2024)
Microbially Induced Carbonate Precipitation (MICP) is recently viewed as one of the approaches for field applications. The goal is to improve the properties of recycled aggregate concrete (RAC), reuse them as well as solve serious global problems such as construction waste, dwindling natural resources, and environmental pollution problems. Typically, the bacteria involved in MICP create urease, causing calcite crystals to form on the surface of grains forming cementation bonds between particles that help in reducing soil permeability and increase overall compressive strength. In this study, the main focus is on assessing the microbial permeability treatment ability of RAC, mainly the MICP treatment process by urease hydrolysis to improve the quality and application of RAC. In addition, the effectiveness of the proposed MICP treatment was determined and the degree of improvement in the permeability treatment properties of the recycled aggregate was evaluated. After performing the MICP treatment, adding Ca2 sources, repeating 3 cycles with a processing time of 24 hours each, evaluating the pore structure at the microscopic level. The results showed that the enzyme activity of urease was directly proportional to the ability to precipitate calcite, which correlated with the ability to improve the permeability of Bacillus thuringiensis strain to RAC through an increase in weight of 13.04% and a decrease in the 43.15% water absorption compared to the control sample.